Effect of Allium Sativum Linn. and Allium Chinense G. Don. on Mortality Rate of Ascaris Suum Eggs - พุทธนา, ริสา; ปั้นดี, วงเดือน; บุญชื่น, สุภาวดี (Journal of health and health management, 2014)
Ascariasis is still a major public health problem in many countries around the world. There was a report which found that garlic could destroy Ascaris eggs. This study, using true experimental 2x5 factorial as its research design, aimed at studying the effect of concentration and type of garlic on mortality rate of Ascaris infective eggs. The study was conducted with Ascaris eggs in Thai and Chinese garlic at 5 concentration levels including 5%, 10%, 15%, 20% and 25%. The Ascaris eggs were counted on the date of 2, 3, 5, 7, 10, 14, 18, 21, 24, 28, 35, 42, 49, 56 and 63 post exposure to five concentrations of garlic. The data were analyzed by t-test and ANOVA. The results revealed that both concentration and type of garlic had an effect on mortality rate of A. suum infective eggs. There was an interaction between type and concentration of garlic in terms of the mortality rate of A. suum infective eggs increased when the concentration of garlic increased and it was higher in Thai garlic. Therefore, the mortality rate of A. suum infective eggs depended on concentrations and types of garlic.